Transport and magnetisation measurements of tl-1223 tapes - the nature of current paths and the role of grain boundaries at high magnetic fields - Everett, J; Johnston, MD; Perkins, G; Volkozub, A; Caplin, A; Moore, J; Fox, S; Hyland, D; Grovenor, C (1997)
The key factors that make the thallium-based 1223 phase conductors attractive candidates for high field applications are a high transition temperature (∼ 115 K), and an irreversibility line comparable to YBa2Cu3O7. However, a third important factor is the grain boundary behaviour. We have made detailed transport current-voltage (I-V) and magnetic studies of a Ag-0. 1%Hf sheathed Tl-1223 tape. For low fields (B < 100 mT) its critical current density Jc performance displays the "weak-link" signatures well-known for polycrystalline YBa2Cu3O7. At high fields however (B > 100 mT) there is a plateau region in its Jc(B) characteristics. Possible scenarios for inter-granular transport current conduction and dissipation in this region are discussed. © 1997 IEEE.